Fitness food: The denial of food taste because of the desired body - Costa , Neuza Cristina Gomes da; Abonizio , Juliana (Seven Editora, 2023)
Among the diversity of dietary practices and nutritional beliefs that coexist in contemporary times, we aim to unravel the relationship between a diet and a body shape, which has become known as fitness culture. To achieve our objective, we conducted eight interviews based on two criteria: self-identification and evidence of body shape that characterizes belonging to the corresponding lifestyle. For a better understanding of the phenomenon, we also performed participant observation in two places frequented by the subjects of the analysis: a bodybuilding gym and a crossfit box, in Cuiabá, Mato Grosso. Through the data constructed, it was possible to identify the use of scientific discourses to defend the effectiveness of a dietary pattern that includes products, ways of preparation, schedules among other variables, considered essential to obtain the desired body shape, hypertrophied and with low fat index. This body, although perceived as an individual responsibility, is supported by discourses of various modalities of health professionals, the media and other members who adopt the same lifestyle. However, we could also assess that the change in eating habits for insertion and acceptance in the fitness universe affects the sociability of the subjects, especially in the family space, but also in the entry and permanence in new groups of peers and withdrawal of old ones. DOI:https://doi.org/10.56238/uniknowindevolp-055